Immature Granulocyte Trajectories Following Hemadsorption as Indicators of Immune Dysregulation and Mortality - Altuntas, Gulsum; Capar, Ayse; Ozcelik, Gulsum; Cakmak, Erkan; Dalkilic, Lutfiye Kadioglu; Demirel, Ismail (Mdpi, 2026)
Background: Sepsis is a life-threatening condition characterized by a dysregulated host response to infection. Hemadsorption therapies remove inflammatory mediators and are used as adjunctive treatment in selected patients. Although increased immature granulocyte (IG) levels correlate with inflammatory severity, changes in IG levels after hemadsorption therapy have not been previously evaluated. Methods: This retrospective observational study included patients with sepsis who received hemadsorption therapy in intensive care units between January 2021 and July 2025. Sepsis was diagnosed according to the Surviving Sepsis Campaign 2021 guidelines, and hemadsorption was initiated for persistent hemodynamic instability despite standard therapy. Treatment was performed using a Jafron HA330 cartridge for at least three 6 h sessions. IG count and percentage, inflammatory parameters, lactate levels, and organ dysfunction scores were recorded before and after therapy. ICU mortality was the primary outcome. Statistical analyses included paired comparisons, multivariable logistic regression, and ROC curve analysis. Results: Among 887 patients with sepsis, 196 met the inclusion criteria. The ICU mortality rate was 43.9%, and the median time between pre- and post-treatment measurements was 4 days (IQR: 3-5). After hemadsorption therapy, IG count, IG%, inflammatory parameters, lactate levels, SOFA scores, and vasopressor requirements decreased (all p-values < 0.001). IG parameters were higher in non-survivors. Post-treatment IG# (AUC 0.880) and IG% (AUC 0.812) showed good discriminative performance. Conclusions: Hemadsorption therapy was associated with reductions in IG parameters and inflammatory indicators in sepsis. These findings support IG parameters as complementary measures of immune and inflammatory dynamics during hemadsorption therapy. Accordingly, this study should be regarded as a hypothesis-generating investigation describing associations of IG dynamics in septic patients undergoing hemadsorption, rather than demonstrating treatment efficacy or causal effects.
Keywords: sepsis; Hemoperfusion; Granulocytes, Immature; intensive care